THE MILITARY ART OF AMIR TEMUR (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents the art of Amir Temur to command the army and highlights the tasks of the units that make up the army during combat operations. At the same time, the combat supply of the army has been analyzed.